Phytochemical Screening and Chemical Compounds of Moringa Oleifera Leaf Hot Water Extract - Siahaan, Tanty Naomi; Basuki; Amir Hamzah (International Journal of Ecophysiology, 2023)
In this study, the phytochemical composition and chemical compounds present in Moringa oleifera leaf hot water extract were investigated. The extraction process involved using hot water to retain a wide range of bioactive constituents. Qualitative and quantitative analyses were employed to characterize the extract's phytochemical profile. Fourier Transform Infrared Spectroscopy (FT-IR) was employed to identify and quantify specific chemical compounds. The phytochemical analysis revealed the presence of various classes of secondary metabolites, including alkaloids, flavonoids, tannins, saponins, terpenoids and phenolics. These bioactive compounds have been associated with antioxidant, anti-inflammatory, and antimicrobial properties. Additionally, the FTIR analysis unveiled a spectrum of chemical constituents, including phenol compounds, flavonoids and alkaloids compounds, known for their potential health benefits. Keywords: Bioactive, Chemical Compounds, Hot Water Extract, Moringa Oleifera, And Phytochemicals